Portable SERS-based breathalyzer for rapid and early-disease detection - Kew, Yi Hong (Nanyang Technological University, 2022)
Cancer is a disease that had taken the lives of many, and it is still one of the leading causes of death in the world. There is still no direct cure for cancer as of today but fortunately, the constant study of the disease over all these years have given us a better understanding on how to reduce the risk of contracting and dealing with it. Although there are various types of cancer, lung cancer is responsible for the highest mortality and mortality rate, and it is also one of the highest diagnosed cancer variants. This could be due to external factors, such as the addiction and availability of tobacco, which could increase the risk of contracting lung cancer. It is widely known that early detection of lung cancer can significantly improve survival rate as it is exponentially higher in the early stages. However, most patients only discover that they have lung cancer in the later stages. This could be due to the lack in availability and the hefty cost for accurate non-invasive detection methods. Therefore, there is a need to devise a non-invasive detection product that can be widely distributed at a low price. A project was started by Silver Factory Technology, and it aimed to create a product that fulfilled the above criteria using the Volatile Organic Compounds in human breath and Silver Nanoparticles. This Final Year Report (FYP) was a subset of the overarching project, and its focus was on creating a Reader System that could integrate the products of all other sub-projects. This FYP report documented the limitations of the project and how they were managed. It also documented in detail the steps that were used to create the design of the Reader System using SolidWorks, before sending the components for fabrication or purchase. The report also stated the various design considerations that were required as the Reader System would need to accommodate for the products of the other sub-projects. Various tests were conducted on the Reader System to ensure that all products were well integrated, and amendments were made to correct features that did not produce the required results.